Arching in soils applied to inclined mine stopes - Ting C.H.; Shukla S.K.; Sivakugan N. (My University, 2025)
Determination of stress distribution, giving due consideration to arching mechanism within minefill stopes, is of great importance because of its influence on the ground stability, ore recovery, and cost effectiveness. Most of the past studies on the stress determination have been applied to vertical stopes, and there is a lack of research study, especially analytical work, on inclined stopes. This study provides an analytical expression for the vertical stress at any depth within the inclined backfilled stopes by incorporating an arching effect within the backfill. Comparatively, the results obtained from this study agree well with other limited analytical and numerical results reported in the literature. A parametric study is undertaken to investigate the effect of various parameters involved in the proposed analytical expression. The results obtained reveal that stope geometry, fill properties, and stope inclination are critical factors in predicting the stress distribution in mine stopes. © 2011 ASCE.